Resolving Bovine viral diarrhea virus subtypes from persistently infected U.S. beef calves with complete genome sequence. (September 2016) - Workman, Aspen M.; Heaton, Michael P.; Harhay, Gregory P.; Smith, Timothy P. L.; Grotelueschen, Dale M.; Sjeklocha, David; Brodersen, Bruce; Petersen, Jessica L.; Chitko-McKown, Carol G.
Bovine viral diarrhea virus (BVDV) is classified into 2 genotypes, BVDV-1 and BVDV-2, each of which contains distinct subtypes with genetic and antigenic variation. To effectively control BVDV by vaccination, it is important to know which subtypes of the virus are circulating and how their prevalence is changing over time. Accordingly, the purpose of our study was to estimate the current prevalence and diversity of BVDV subtypes from persistently infected (PI) beef calves in the central United States. Phylogenetic analysis of the 5′-UTR (5′ untranslated region) for 119 virus strains revealed that a majority (82%) belonged to genotype 1b, and the remaining strains were distributed between genotypes 1a (9%) and 2 (8%); however, BVDV-2 subtypes could not be confidently resolved. Therefore, to better define the variability of U.S. BVDV isolates and further investigate the division of BVDV-2 isolates into subtypes, complete genome sequences were obtained for these isolates as well as representatives of BVDV-1a and -1b. Phylogenetic analyses of the complete coding sequence provided more conclusive genetic classification and revealed that U.S. BVDV-2 isolates belong to at least 3 distinct genetic groups that are statistically supported by both complete and individual coding gene analyses. These results show that a more complex set of BVDV-2 subtypes has been circulating in this region than was previously thought.